Effect of pulse flours on the physiochemical characteristics and sensory acceptance of baked crackers. (29th March 2017) - Millar, Kim Adrienne; Barry‐Ryan, Catherine; Burke, Róisín; Hussey, Karen; McCarthy, Sinéad; Gallagher, Eimear
Summary: Pulse flours offer nutritional alternatives to wheat flour in the production of baked snacks due to their high protein and fibre levels and low glycaemic index. In this study, broad‐bean ( Vicia faba ), yellow‐pea and green‐pea ( Pisum sativum ) flours were each blended with wheat flour at 40% in the formulation of chemically leavened crackers. The effects of flour type and baking time on the physiochemical properties, sensory acceptability, nutritional composition and antioxidant activity of the crackers were observed in comparison with 100% wheat crackers. Broad‐bean crackers had the highest protein content and antioxidant activity (13 g per 100 g DM and 38.8 mgAAE per 100 g DM, respectively). Yellow‐pea crackers had the highest fibre content (12 g per 100 g DM). Physical dimensions and colour attributes were significantly affected by pulse‐flour substitution. Yellow‐pea and broad‐bean crackers were significantly preferred by consumers compared to the control, demonstrating the potential application of these flours to improve the eating quality and nutritional profile of crackers. Abstract : Sensory evaluation of consumer preference with respect to appearance and eating quality: Panellists scored using a 9‐point hedonic scale, where 9 = like extremely, 5 = neither like nor dislike, 1 = dislike extremely. Control: wheat only crackers, BB: wheat‐broad‐bean crackers, YP: wheat‐yellow‐pea crackers, GP: wheat‐green‐pea crackers.